Voices from the Margins: Low-income Fatherhood in the Era of Neoliberalism. - Black, Timothy; Keyes, Sky (Humanity & Society, 2021)
The norms and expectations of "father involvement" have changed rapidly within a generation, and yet, the labor force and state institutions have not supported low-income families in a way to achieve this. In this article, we examine the narratives of 138 socially and economically marginalized fathers to identify the frames that they adopt to represent themselves as fathers, tell a coherent story about their lives, and project an identity of themselves into their futures. Despite the political–economic forces that have dramatically increased inequality in an era of neoliberal capitalism, fathers rarely alluded to structural explanations for family instability, father absence, marital dissolution, and gender distrust in low-income communities. Instead, fathers attempted to adopt socially valued identities along three symbolic boundaries that distinguished themselves from their own fathers, from welfare frauds, and from the iconic deadbeat dad. They also adopted individualistic frames that took the form of therapeutic narratives and life-course transitional narratives. In general, despite harsh structural constraints, the men imagined themselves doing better, and, in nearly all cases, being engaged fathers was at the center of these hopeful constructions. Without structural change, however, these aspirational frames are likely to become little more than false hopes.